STRATEGI PEMBELAJARAN ANAK AUTISME DI SEKOLAH LUAR BIASA: TINJAUAN OBSERVASI DAN WAWANCARA - Mariana Agustina Turnip; Hariyanti, Riris; Diah Fitriani; Agung Ramadhan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe learning strategies for children with autism in Special Needs Schools (SLB) through observation and interviews. The focus of the study was directed at the characteristics of children with autism, the types of learning strategies implemented by teachers, and the supporting and inhibiting factors in the learning process. This study used qualitative methods with a descriptive approach. The subjects consisted of one student with Autism Spectrum Disorder (ASD) and his/her accompanying teacher at the Taman Pendidikan Islam Medan Special Needs School. Data collection techniques included direct observation during learning activities and in-depth interviews with the teacher. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the implemented learning strategies were individualized and structured, including one-teacher-one-child mentoring, the use of a modified curriculum, simple instructions, visual media, and a positive reinforcement system. These strategies were able to improve children's focus, learning responses, and emotional control during learning. However, the study also identified obstacles such as limited facilities, the absence of a Special Needs Teacher, and the child's internal conditions that impacted learning stability. Parental support and collaboration with the school are important factors in supporting child development. Therefore, adaptive, individualized and collaborative learning strategies are considered effective in supporting the learning process for children with autism in SLB.